Efficiency and safety of varying the frequency of whole blood donation: randomised trial of 45,000 donors - Di Angelantonio, E; Thompson, S; Kaptoge, S; Moore, C; Walker, M; Armitage, J; Ouwehand, W; Roberts, D; Danesh, J (Lancet, 2017)
Background Limits on the frequency of whole blood donation exist primarily to safeguard donor health. However, there is substantial variation across blood services in the maximum frequency of donations allowed. We compared standard practice in the UK with shorter inter-donation intervals used in other countries. Methods 45,263 whole blood donors were recruited between 2012 and 2014 from 25 centres across England (ISRCTN24760606). Using a computer-based algorithm, 22,466 men were randomly assigned to 12-week (standard) versus 10-week versus 8-week inter-donation intervals, while 22,797 women were randomly assigned to 16-week (standard) versus 14-week versus 12-week intervals. Participants were not blinded to their allocated intervention group. The primary outcome was the number of donations over two years. Secondary outcomes related to safety included quality of life, donation-related symptoms, physical activity, cognitive function, haemoglobin and ferritin levels, and deferrals due to low haemoglobin. Findings In men, compared to the 12-week group, the mean amount of blood collected per-donor over 2-years increased by 1.69 (95% CI: 1.59-1.80) units in the 8-week group and 0.79 (0.69-0.88) units in the 10-week group. In women, compared to the 16-week group, it increased by 0.84 (0.76-0.91) units in the 12-week group and 0.46 (0.39-0.53) units in the 14-week group (P<0.0001 for each). No significant differences were observed in quality of life, physical activity, or cognitive function across randomised groups. However, more frequent donation resulted in more donation-related symptoms (eg, tiredness, breathlessness, feeling faint, dizziness, and restless legs, especially among men), lower mean haemoglobin and ferritin levels, and more deferrals for low haemoglobin (P<0.0001 for each). Interpretation Over two-years, more frequent donation than is standard practice in the UK collected substantially more blood without major impact on donors’ quality of life, physical activity, or cognitive function, but resulted in more symptoms, deferrals, and iron deficiency.